2019
DOI: 10.1108/jkm-07-2018-0414
|View full text |Cite
|
Sign up to set email alerts
|

When knowledge management matters: interplay between green human resources and eco-efficiency in the financial service industry

Abstract: Purpose Drawing on the ability–motivation–opportunity theory applied to the greening of service industries, this paper aims to analyze the extent to which green human resource management plays a role in the adoption of eco-efficiency principles in the financial sector. Environmental knowledge management represents one of the key green human resource management components. Design/methodology/approach This study conducted a survey with 178 employees working within one of the largest financial banks in Brazil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…By adopting GHRM practices, the organization sends a clear message to its employees: it is committed to the social green cause beyond any financial benefits. According to Renwick et al (2013), three GHRM practice components -subsequently taken on and applied by other scholars-may be used: a) developing green abilities (recruitment, selection, training, and development); b) motivating green employees (performance management/appraisal; pay and reward system); and c) providing green opportunities (employee involvement and supportive climate/culture) (Moraes et al, 2018;Tang et al, 2018). An attempt will be made in this research to disaggregate those three components into the following GHRM practices: recruitment and selection, training, performance management, rewarding, and involvement that aim to build green values as well as knowledge and skills related to green activities (Pless, Maak, & Stahl, 2012;Renwick, Redman, & Maguire, 2013;Tang, Chen, Jiang, Paillé, & Jia, 2018).…”
Section: Studies Focused On Analyzing How Crs Contributes To Hr Practices Include Those Bymentioning
confidence: 99%
“…By adopting GHRM practices, the organization sends a clear message to its employees: it is committed to the social green cause beyond any financial benefits. According to Renwick et al (2013), three GHRM practice components -subsequently taken on and applied by other scholars-may be used: a) developing green abilities (recruitment, selection, training, and development); b) motivating green employees (performance management/appraisal; pay and reward system); and c) providing green opportunities (employee involvement and supportive climate/culture) (Moraes et al, 2018;Tang et al, 2018). An attempt will be made in this research to disaggregate those three components into the following GHRM practices: recruitment and selection, training, performance management, rewarding, and involvement that aim to build green values as well as knowledge and skills related to green activities (Pless, Maak, & Stahl, 2012;Renwick, Redman, & Maguire, 2013;Tang, Chen, Jiang, Paillé, & Jia, 2018).…”
Section: Studies Focused On Analyzing How Crs Contributes To Hr Practices Include Those Bymentioning
confidence: 99%
“…In this context, it worth highlighting that concepts such as cleaner production, social responsibility, and eco-innovation contribute to meet sustainability guidelines, in which issues related to environmental awareness and the sustainable consumption of natural resources and human capital enhance the achievement of a more sustainable future (Maruyama et al, 2019;Severo et al, 2018). Moreover, cultural aspects must also be considered, since they play an important role for companies to achieve the transdisciplinary concept of sustainability (Moraes et al, 2018;Roscoe et al, 2019;Singh and Singh, 2018).…”
Section: Sustainabilitymentioning
confidence: 99%
“…This segment highlights the factors that are needed to execute green HRM practices. Findings suggests that various studies were performed to determine the executing factors like Hameed, Khan [29] and Tariq, Jan [38] identified green employee empowerment, Yong, Yusliza [39] highlighted on green intellectual capital, Paillé , Chen [40] emphasized on OCBE, Obeidat, Al Bakri [41] stressed on top management support, Moraes Silvana de, Chiappetta Jabbour Charbel [42] considered knowledge management. Moreover Teixeira, Jabbour [43] identified that collaboration, coordination and integration of top management commitment, environmental supportive organizational culture and teamwork are the pioneer factors of green HRM.…”
Section: Factors Of Green Hrm: An Overviewmentioning
confidence: 99%
“…Moreover, other theory at firm level [48,88] used stakeholder theory. Other theories that were used are [44,85] tested signaling theory, Sawang and Kivits [71] used theory of planned behavior to judge top management attitude towards being environmental responsible, AMO theory by [42,67], Luu [79] used attribution theory and O'Donohue and Torugsa [86] used absorptive capacity theory.…”
Section: Green Hrm Paradigm In Terms Of Underpinning Theoriesmentioning
confidence: 99%